2020
DOI: 10.3389/fendo.2020.00474
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of ApoC-III on the Metabolism of Triglyceride-Rich Lipoproteins in Humans

Abstract: Cardiovascular disease (CVD) is the leading cause of death globally. It is well-established based on evidence accrued during the last three decades that high plasma concentrations of cholesterol-rich atherogenic lipoproteins are causatively linked to CVD, and that lowering these reduces atherosclerotic cardiovascular events in humans (1-9). Historically, most attention has been on low-density lipoproteins (LDL) since these are the most abundant atherogenic lipoproteins in the circulation, and thus the main car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 149 publications
2
82
0
Order By: Relevance
“…6 ). A decrease in circulating Tgs and remnant cholesterol particles, less accumulation of atherogenic lipoproteins in the artery wall, and reduced endothelial inflammation result in a diminished risk for CVD ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…6 ). A decrease in circulating Tgs and remnant cholesterol particles, less accumulation of atherogenic lipoproteins in the artery wall, and reduced endothelial inflammation result in a diminished risk for CVD ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, apoCIII gene expression is negatively regulated by insulin, which represses the activity of the apoCIII promoter activity via inhibition of the insulin/phorbol ester responsive element (IRE) within the apoCIII gene [ 42 , 43 , 44 ]. The inhibitory action of insulin on the gene expression is mediated by the nuclear transcription factor forkhead box O1 (Foxo1), known as signal transductor of insulin for liver gluconeogenesis [ 38 , 45 , 46 ].…”
Section: Apociii Gene Regulationmentioning
confidence: 99%
“…Apo-CIII is a novel potential drug target in the management of cardiovascular disease driven by multiple studies demonstrating that plasma levels of apo-CIII are predictive of coronary heart disease and the risk of disease-related events (Borén et al, 2020). Previously, it has been shown that sialylated apo-CIII glycoforms are differentially cleared by hepatic receptors and that a higher apo-CIII 2 /apo-CIII 1 ratio is associated with improved triglyceride levels (Kegulian et al, 2019).…”
Section: Discussionmentioning
confidence: 99%